Évaluation du risque sanitaire de sols pollués méditerranéens : choix de variables et spatialisation - Aurélie Arnaud; Pascale Prudent; Isabelle Laffont-Schwob (VertigO)
The concept of health risk needs to be compared with the notions of hazard, vulnerability, capacity and danger so as to consider it in an integrative way and choose appropriate variables for its spatialization. In this multidisciplinary reflection, we particularly questioned "how to integrate the physical sensitivity of the population when considering soil pollution in order to locate the most vulnerable areas in a context of health risk ? ". The Marseilleveyre massif located south of Marseille (Bouches-du-Rhône) is adequate object of study for both semantic and spatial enforcements. Highly contrasted in its issues, this territory is at the same time included in the core area of the Calanques National Park (PNCal) and remains affected by a diffuse soil pollution resulting from past industrial activities located on the coast. This core area of the PNCal is however inhabited in its periphery and welcomes many users. A model of generalization of the methodology developed in this case study is then proposed in order to perform this production and this mode of visualization of the information which could constitute a precious base of aid to the consultation.